Mitochondrial fission genes MTFP1/MTFP2 as predictive biomarkers in prostate cancer: a mendelian randomization study - Xuejun Huangfu; Zhiqiang Fan; Jia Zheng; Jiabei Xie (Discover Oncology)
Abstract Background Mitochondrial dynamics, particularly the balance between fission and fusion, play a crucial role in cancer progression, including prostate cancer, by influencing cellular metabolism and survival. MTFP1 and MTFP2 are key regulators of mitochondrial fission, and their roles in prostate cancer warrant further investigation. Methods We conducted a comprehensive bioinformatics analysis using RNA-seq data from The Cancer Genome Atlas (TCGA) and SNP data from the UK Biobank (ukb-b-13348) GWAS dataset. Differential gene expression analysis was performed using the limma package, and pathway enrichment analysis was conducted using clusterProfiler. Hub genes were ranked using the CytoHubba algorithms. MCC was prioritized due to its robustness in identifying fully connected subgraphs. Mendelian Randomization (MR) analysis was performed using the TwoSampleMR package to assess the causal relationships between identified hub genes and prostate cancer. Results The analysis revealed significant differential expression of MTFP1 and MTFP2 between tumor and adjacent normal tissues, with MTFP2 showing a highly significant upregulation (p-value = 7.06e-06) and an AUC of 0.698, suggesting its potential as a biomarker. In the MR analysis, several hub genes, including ANLN, CDC45, CDCA2, and KIF15, were identified as having a significant causal relationship with prostate cancer, with effect estimates ranging from − 0.03 to 0.15 and statistically significant p-values. These findings suggest that mitochondrial dynamics and related pathways play a critical role in prostate cancer pathogenesis. Conclusion The study highlights the potential diagnostic and prognostic value of mitochondrial fission-related genes, particularly MTFP2, in prostate cancer and underscores the importance of further investigating these pathways as therapeutic targets.